Using Scrabble Game-Based Learning to Improve English Vocabulary Mastery: A Systematic Review - Afaniya Ika Aulin Farich; Sri Wahyuni (LPPM Universitas Advent Indonesia, 2025)
This study aims to systematically examine the effectiveness of Scrabble as a game-based learning tool in enhancing students’ English vocabulary mastery. Vocabulary acquisition is a foundational component of English as a Foreign Language (EFL) learning; however, conventional methods often fail to engage students meaningfully. Scrabble has emerged as an educational game that combines linguistic strategy, interactivity, and contextual learning, making it a promising alternative to traditional approaches. Employing a Systematic Literature Review (SLR) method guided by the PRISMA framework, the researchers identified and evaluated 30 eligible studies conducted in Indonesia between 2020 and 2025. These studies were selected based on relevance to Scrabble’s application in vocabulary instruction across elementary to tertiary education levels. The review found consistent evidence that Scrabble improves vocabulary mastery by increasing learner motivation, engagement, retention, and contextual understanding. Supporting factors include the game's interactive nature, adaptability to various learning levels, and ability to foster collaborative and student-centered environments. However, inhibiting factors such as initial rule confusion, classroom management challenges, and limited digital literacy among teachers may reduce its effectiveness if not addressed through proper implementation strategies. Substantially, this review concludes that Scrabble is a flexible and pedagogically sound method for vocabulary enhancement, provided that educators apply structured guidance and inclusive practices. The findings offer valuable insights for teachers, curriculum designers, and educational policymakers seeking to integrate innovative, game-based strategies into EFL instruction